Requirements and general architecture of a payment system for the Future Internet - Wilusz, Daniel; Rykowski, Jarogniew (Wymagania i architektura systemu płatności w Internecie Przyszłości, 2012)
The advent of the Future Internet contributes to the emergence of new markets of physical objects offering their services. This phenomenon leads to new human-to-machine (H2M) and even machine-to-machine (M2M) markets, which require new payment methods. The goal of the paper is twofold. First, the requirements for a payment system in the Future Internet are identified and discussed, with the emphasis on system efficiency. Second, we propose a novel architecture of a payment system meeting the requirements of the Future Internet. The aim of our proposal is to design an efficient, anonymous, semi-off-line micropayment system by the application of cryptographic techniques as well as proper data exchange among system participants. The main principle of the proposal is the assumption that the system should be designed in such a way that it is pointless for both the payer as well as the payee to behave in a fraudulent way
Informatyka Ekonomiczna = Business Informatics, Nr 2 (24), s. 91-103
Keywords: micropayments; electronic money; Future Internet